Initiating Sustainable Development Goals (SDGs) for Village: A Joint International Community Service Program - Ashoer, Muhammad; Alam, Syamsu; Pramukti, Andika; Lanceleur, Victor; Solene, Davoine (Penerbit Goodwood, 2023)
Purpose: The purpose of this program is to provide a basic understanding of the advantages inherent in implementing Sustainable Development Goals (SDGs) in rural areas, particularly in Padanglampe Village, South Sulawesi, Indonesia. Methodology: We employ socialization to deliver a fundamental understanding of the SDGs within Padanglampe Village. This approach is divided into three steps. First, lectures on SDGs and their relevance to village development were delivered to the participants. The speakers are lecturers from the Faculty and Economics and Business, Universitas Muslim Indonesia, and exchange students, Victor Lanceleur and Davoine Solene, from Polytech Annecy-Chambéry-Université Savoie Mont Blanc, France. Second, interactive Q&A sessions are conducted to foster active engagement. Finally, participant knowledge, awareness, and attitudes towards SDGs were evaluated using a questionnaire-based approach. Results: The study involved 29 participants from diverse backgrounds, and, overall, the program progressed smoothly. Evaluation findings indicate that the majority of participants in Padanglampe village attained adequate literacy regarding SDGs following lectures. This suggests a positive impact of the program in enhancing knowledge, awareness, and attitude among villagers about the SDGs and their significance for sustainable development. Limitations: Although the program showed promising results, certain limitations need to be addressed. One notable limitation is the reliance on Google Forms for evaluation, which may not provide a comprehensive understanding of the participants’ perspectives. Therefore, we strongly suggest using participatory approaches, such as interviews, to obtain deeper insights into villagers’ understanding and perceptions of the SDGs. Contributions: Despite these limitations, this community service program initiative has made significant contributions to advancing villagers’ understanding and participation in SDGs. By providing socialization about SDGs at the grassroots level, the program has played a crucial role in promoting sustainable development within rural areas.